2021
DOI: 10.3390/su132112150
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential for Utilization of Medium and Highly Sulfidic Mine Tailings in Construction Materials: A Review

Abstract: Medium and highly sulfidic tailings are high-volume wastes that can lead to severe environmental damage if not properly managed. Due to the high content of sulfide minerals, these tailings can undergo weathering if put in contact with oxygen and water, generating acid mine drainage (AMD). The moderate-to-high sulfide content is also an important technical limitation for their implementation in the production of construction materials. This paper reviews the use of sulfidic tailings as raw material in construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 166 publications
0
16
0
Order By: Relevance
“…This solid residue, however, still contains small quantities of residual metals and offers potential for further extraction processes before being stored or, given its rich mineral content, reused as a replacement for raw materials in building material or inorganic polymers. 13,15,16 • MW-assisted hydrothermal iron-precipitation: in previous works, it has been shown that MW-assisted hydrothermal reactions are more efficient through enabling rapid, uniform, and selective heating and a simpler, more environmentally friendly performance. Compared to conventional hydrothermal methods, which often require harsh temperature and pressure conditions, as well as longer times (hours to days), MWassisted hydrothermal processes operate under lower temperatures and pressures as well as shorter times (minutes to hours).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This solid residue, however, still contains small quantities of residual metals and offers potential for further extraction processes before being stored or, given its rich mineral content, reused as a replacement for raw materials in building material or inorganic polymers. 13,15,16 • MW-assisted hydrothermal iron-precipitation: in previous works, it has been shown that MW-assisted hydrothermal reactions are more efficient through enabling rapid, uniform, and selective heating and a simpler, more environmentally friendly performance. Compared to conventional hydrothermal methods, which often require harsh temperature and pressure conditions, as well as longer times (hours to days), MWassisted hydrothermal processes operate under lower temperatures and pressures as well as shorter times (minutes to hours).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The removal of sulfur in the form of SO x gases (during roasting) and sulfates (during leaching) in a controlled manner significantly reduces the environmental risks of sulfidic tailings since it decreases the risk of AMD after depositing the produced leaching residues. This solid residue, however, still contains small quantities of residual metals and offers potential for further extraction processes before being stored or, given its rich mineral content, reused as a replacement for raw materials in building material or inorganic polymers. ,, MW-assisted hydrothermal iron-precipitation: in previous works, it has been shown that MW-assisted hydrothermal reactions are more efficient through enabling rapid, uniform, and selective heating and a simpler, more environmentally friendly performance. Compared to conventional hydrothermal methods, which often require harsh temperature and pressure conditions, as well as longer times (hours to days), MW-assisted hydrothermal processes operate under lower temperatures and pressures as well as shorter times (minutes to hours). When applied to the aqueous leachates generated in our process, selective precipitation of Fe with adsorbed As was achieved within 1 h at 150 °C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of ye'elimite (Ca 4 (AlO 2 ) 6 SO 3 ) as active clinker phase instead of alite (Ca 3 SiO 5 ) brings advantages in decreasing firing temperature by 100 • C -250 • C during clinkerization of CSA cement (Telesca et al, 2019). The inventory input for clinker materials is modeled based on Martins et al (2020Martins et al ( , 2021, where highly sulfidic tailings constitute 14%-wt of raw meal mixture. To generate the entire life cycle model at a large scale, we combine our design mix with the industrial CSA plant data.…”
Section: Calcium Sulfoaluminate Productionmentioning
confidence: 99%